Seaqir Covid -19 Mathematical Modell - Fira Adila, Fira Adila; Arnellis (Department of Mathematics, Universitas Negeri Padang (UNP), 2023)
This research discusses the mathematical model of Covid-19 disease. The model formed consists of 6 components, namely Susceptible (S), Exposed (E), Asymptotically Infected (A), Quarantined (Q), Symptomatic Infected (S), and Recovered (R). This research aims to determine the local stability analysis of the model formed. Apart from that, the R0 value of the model is also looked for. The model stability analysis was carried out in disease-free and endemic settings by showing asymptotic stability. Based on the analysis results obtained. The primary reproduction number for disease-free and endemic simulations is greater than 1. The interpretation of the COVID-19 mathematical model from the stability analysis shows that COVID-19 will still exist for a specific time and will not disappear.